Pemberdayaan Siswa dan Siswi SMA Plus Muhammadiyah Kota Subulussalam Melalui Program Bimbingan Belajar KPM DRI Selama Pandemi Covid-19 - Cahyadi Cibro, Aldi; Januar, Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
One of the problems experienced by some SMA Plus Muhammadiyah students in the city of Subulussalam is a lack of awareness of the potential of each individual, which if they maximize this potential it can be used as additional resources to produce a positive impact on themselves even for the surrounding crowd. One of the programs implemented to increase the potential of SMA Plus Muhammadiyah students is KPM DRI tutoring during the Covid-19 pandemic. This activity was held with the aim of 1) to build students' awareness of the importance of science. 2) to create and realize quality human resources with character, creative and innovative potential. 3) to encourage students to be more enthusiastic about learning and achieving brilliant achievements. The expected result through the KPM DRI tutoring program during the Covid-19 pandemic is an increase in the enthusiasm of students to be more active in exploring their potential. In addition, the KPM DRI tutoring program during the Covid-19 pandemic can also help students who have difficulty doing school assignments given while doing routine learning in class.